Effect of Al2O3 Particles and Precipitation Hardening on the Properties of Cast 332 Aluminum Alloy - Subhi, Akeel Dhahir; Abdullah, Hussein Najim (Al-Khwarizmi Engineering Journal, 2018)
In this work, 332 Al alloy was prepared and reinforced with (0.5% and 1%) nano-Al2O3 particles. The prepared unreinforced and reinforced 332 Al alloy with nano-Al2O3 were solution heat treated (T6) at 510 ̊C and aged at 225 ̊C with different times (1, 3, and 5 h). Hardness test was performed on all the prepared alloys. All prepared alloys were dry slided under different applied loads (5, 10, 15, and 20 N) against steel counterface surface using pin on disk apparatus. The results showed that refinement effect was observed after addition of nano-Al2O3 particles and a change in silicon morphology after performing the solution heat treatment. The results also showed that hardness was increased and the wear rate was decreased with increasing the nano-Al2O3 particles in the matrix of 332 Al-Alloy